Produção e Caracterização de Filme de a-C:H(N) - Souza, Alan Roger Moreno (2018)
The great interest in using diamond-like carbon (DLC) thin films is justified by their remarkable properties. The DLC film may incorporate other atomic elements depending on the precursor gas and the deposition conditions of the films, which provide different optical and mechanical properties to the film. The incorporation of nitrogen in the DLC film (a-C:H(N)) causes the decrease in the amount of carbon atoms in the state of hybridization sp3 and decreases the internal tension of the film, thus increasing the adhesion of the film to the substrate. Therefore the deposition parameters were studied in order to avoid high internal stresses present in the films that impair its adhesion to the metallic substrate and promote properties of interest. The objective of this work was to produce and study the effect of nitrogen incorporation in DLC (a-C:H) films on their chemical, mechanical and structural properties. The a-C: H and a-C: H (N) films were deposited on glass substrates, titanium alloy (Ti6Al4V) and cobalt (WC-Co) carbide machining tool. The plasma-assisted vapor deposition technique (PECVD) using DC-pulsed source was used as the precursor methane gas with dilute argon, for the reproduction of a-C:H film, and nitrogen diluted in methane gas for the production and characterization of the aC:H(N) film. Studies on the physical cleaning, deposition of the interlayer film (a-Si), growth of a-C:H(N) film and study of the incorporation of nitrogen into the a-C:H film were made. For the characterizations, the techniques of visual evaluation, Fourier Transform Infrared Spectroscopy (FTIR), profilometry, dispersive energy spectroscopy (EDS) using scanning electron microscopy (SEM), Raman spectroscopy, photoelectron spectroscopy, X (XPS), nanoindentation and machining test. The results obtained were a-C:H and a-C:H(N) adherent films. The adhesion, deposition rate and mechanical and optical properties of DLC films are related to the following parameters: total gas flow, gas ratio, power, temperature and pre-treatments used, such as physical cleaning and deposition of silicon interlayer films. The physical cleaning of the substrate showed the best result when the concentration of the argon and hydrogen gases were made in equal proportions and with total gas pressure of approximately 2 Torr. The a-C:H film had a hydrogen concentration of 26.64%, hardness of 14 GPa and 39.1% of sp3 hybridization between carbons. With the characteristics described the film produced can be classified as a hard film of a-C:H, according to previous research (Robertson, 2002). For the a-C:H(N) films the increase in the amount of nitrogen incorporated into the film was observed with the increase in the N2 gas flow diluted during the treatment. The concentration increased from 2 to 8% when the proportion of nitrogen inserted during the treatment was increased, from 10 to 60%, respectively. It was observed the increase in the deposited film thickness when the nitrogen was inserted diluted concentrations of 10 to 40% in methane, but in nitrogen concentrations higher than 50 and 60%, the deposition rate decreased. The spectra obtained by FTIR showed C-C and C-H2 bonds with most sp3 bonds for the a-C:H film, while the presence of nitrogen bands was found for the a-C:H (N) film. For characterization by Raman spectroscopy, the change of the position of the G band to higher wave numbers denote the decrease of carbon with hybridized bonds sp3, this is due to the increase of the incorporation of nitrogen in the film. No significant change in film hardness was observed with different nitrogen incorporations. In the milling test, it was observed that, among the a-C:H(N) films produced, the film with a 20% dilution of nitrogen in methane provided a longer life for the cutting tool. The tool with no film deposition with a life of 6.2 minutes and the tool with a-C:H(N) film with 8.1 minutes of machining. However, the a-C:H film still had the best tool life with its total machining time of 9.2 minutes. The test specimen presented lower surface roughness for the tools with the deposition of DLC film when compared to the test body machined with the tool without deposition.